2015
DOI: 10.1007/s00264-015-2903-7
|View full text |Cite
|
Sign up to set email alerts
|

Locking compression plate as an external fixator in the treatment of closed distal tibial fractures

Abstract: Locking compression plates can be used as external fixators and provide a high rate of union, comfortable clinical course and excellent ankle-joint motion. Although indications are limited, this method is a suitable surgical approach for treating closed distal tibial fractures with soft tissue compromise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…However, the application of supercutaneous plating technique is still not generally acknowledged. Recently, many authors [ 3 , 14 – 21 ] reported the good clinical results of using external locked plating for treating tibial fractures. Thus, we systematically reviewed the published literature on the biomechanics, outcomes, and complications of the locking plate used as an external fixator to treat fractures of the tibia.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of supercutaneous plating technique is still not generally acknowledged. Recently, many authors [ 3 , 14 – 21 ] reported the good clinical results of using external locked plating for treating tibial fractures. Thus, we systematically reviewed the published literature on the biomechanics, outcomes, and complications of the locking plate used as an external fixator to treat fractures of the tibia.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of applying open reduction and internal xation were that the fracture site could be exposed su ciently and the reduction could be ful lled anatomically under direct vision. Researchers [3,[15][16][17] reported that the deformed union rate of fractures after plate xation was less than 10%, but the risk of postoperative complications with soft tissues was higher, including super cial infections, deep infections, delayed wound healing, and necrosis of soft tissues. In the early 1940s, the intramedullary nail system was introduced to treat tibial shaft fractures, which can reduce the deformity union for tibial fracture and decrease the formation of pseudo-articular joints after the surgery, meanwhile promote the ossi cation of fractured callus.…”
Section: Discussionmentioning
confidence: 99%
“…LCPs have recently been used as a substitute for traditional external fixators, and have proved to be a highly popular alternative in the management of open fracture [ 12 16 ], infected nonunion [ 8 10 , 17 , 22 ], and even closed fracture of the tibia [ 11 , 23 , 24 ]. Locking screws can lock directly into the plate to obtain a stable connection instead of relying on friction between the plate and the bone, which is similar to the principle of external fixation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, pin tract infection was only seen in one screw of one patient. We attribute this extraordinarily low rate of pin tract infection to fully-threaded titanium screws that had better biological compatibility and adhered more easily to the skin compared with the partially-threaded stainless steel Schanz screws used in traditional external fixation [ 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%